Permalasahan Media Pembelajaran IPS Yang Kurang Variatif Dan Strategi Pemecahannya - Shella Rhodinia; Selly Triamanda; Bagus Setiawan; Abdul Aziz (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Learning media has a very important role in the educational process. The problem of learning media in Social Sciences (IPS) subjects is that it is less varied. The reason is due to a lack of learning facilities, educators find it difficult to offer a variety of learning resources. Additionally, there is a scarcity of reading materials and teachers find it difficult to innovate effective teaching solutions. The solution that is considered appropriate to overcome this problem is to utilize varied media. Utilization of varied media in making progress through students searching for and finding ideas with or with help. This article can help with the problem of less varied learning media because you can see the strategies and their implementation. The purpose of writing this article is to describe (1) the causes of less varied social studies learning media (2) solution strategies (3) application of learning strategies (4) variations in social studies teaching materials.